Bacterial precursors and unsaturated long-chain fatty acids are biomarkers of North-Atlantic deep-sea demosponges. - Anna de Kluijver; Klaas G J Nierop; Teresa M Morganti; Martijn C Bart; Beate M Slaby; Ulrike Hanz; Jasper M de Goeij; Furu Mienis; Jack J Middelburg (PLoS ONE, 2021)
Sponges produce distinct fatty acids (FAs) that (potentially) can be used as chemotaxonomic and ecological biomarkers to study endosymbiont-host interactions and the functional ecology of sponges. Here, we present FA profiles of five common habitat-building deep-sea sponges (class Demospongiae, order Tetractinellida), which are classified as high microbial abundance (HMA) species. Geodia hentscheli, G. parva, G. atlantica, G. barretti, and Stelletta rhaphidiophora were collected from boreal and Arctic sponge grounds in the North-Atlantic Ocean. Bacterial FAs dominated in all five species and particularly isomeric mixtures of mid-chain branched FAs (MBFAs, 8- and 9-Me-C16:0 and 10- and 11-Me-C18:0) were found in high abundance (together ≥ 20% of total FAs) aside more common bacterial markers. In addition, the sponges produced long-chain linear, mid- and a(i)-branched unsaturated FAs (LCFAs) with a chain length of 24‒28 C atoms and had predominantly the typical Δ5,9 unsaturation, although the Δ9,19 and (yet undescribed) Δ11,21 unsaturations were also identified. G. parva and S. rhaphidiophora each produced distinct LCFAs, while G. atlantica, G. barretti, and G. hentscheli produced similar LCFAs, but in different ratios. The different bacterial precursors varied in carbon isotopic composition (δ13C), with MBFAs being more enriched compared to other bacterial (linear and a(i)-branched) FAs. We propose biosynthetic pathways for different LCFAs from their bacterial precursors, that are consistent with small isotopic differences found in LCFAs. Indeed, FA profiles of deep-sea sponges can serve as chemotaxonomic markers and support the concept that sponges acquire building blocks from their endosymbiotic bacteria.